2022
DOI: 10.2147/cia.s344689
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of the “Identification of Seniors at Risk” Score on Mortality, Length of Stay, Mobility and the Destination of Discharge of Geriatric Hip Fracture Patients

Abstract: Purpose The German Society for Geriatrics recommends the “ISAR” questionnaire as a screening tool for patients ≥70 for geriatric screening in emergency rooms. Although the ISAR-score is collected routinely in the “AltersTraumaRegister DGU ® ” (ATR-DGU), to date less is known about the predictive value of the “ISAR”-score in geriatric trauma patients. Patients and Methods Currently, 84 clinics participate in the ATR-DGU. This evaluation is limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Dingley et al (2022) reported that as the ISAR score increases, so does the need for discharge to an SNF. Similarly, Knauf et al concluded that a positive ISAR score (≥2) in hip fracture patients predicted an increased risk of being discharged to an SNF (Knauf et al, 2022). Discharging patients to an SNF or a subacute rehabilitation (SAR) facility is the typical plan of care for a patient admitted for a hip fracture at the study site, contrary to Gronewold et al (2017), who reported rare discharges to SNF and/or SAR facilities in patients who were admitted to the orthopedics and trauma surgery.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Dingley et al (2022) reported that as the ISAR score increases, so does the need for discharge to an SNF. Similarly, Knauf et al concluded that a positive ISAR score (≥2) in hip fracture patients predicted an increased risk of being discharged to an SNF (Knauf et al, 2022). Discharging patients to an SNF or a subacute rehabilitation (SAR) facility is the typical plan of care for a patient admitted for a hip fracture at the study site, contrary to Gronewold et al (2017), who reported rare discharges to SNF and/or SAR facilities in patients who were admitted to the orthopedics and trauma surgery.…”
Section: Resultsmentioning
confidence: 98%
“…This variability includes screening performed by differing providers (nursing staff, residents, and advanced practice providers) and the frequency in which patients were assessed using the screening tool (within 24–72 hr of admission, twice a week, and daily). Inzitari et al (2015) utilized a cutoff score of 3 as a positive ISAR score, whereas others considered 2 as warranting a geriatric evaluation (Asomaning & Loftus, 2014; Dingley et al, 2022; Edmans et al, 2013; Gronewold et al, 2017; Knauf et al, 2022). To the existing body of literature, this study adds outcomes stratified by each ISAR score for patients with hip fractures and the outcomes associated with geriatric evaluations using the score with a cutoff of 2 as a trigger for the evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ISAR score cut-off of 2 indicates a low-risk group with safe discharge of geriatric patients. ISAR maximum score of 6 indicates a very high-risk group that needs further assessment and follow-up of the hospitalized patient [ 7 ]. The length of stay of hospitalized geriatric patients, from admission to discharge, was also documented.…”
Section: Methodsmentioning
confidence: 99%
“…It's ideal for correcting the underlying pathology; thereby, sodium and total body water composition is maintained [ 6 ]. Hyponatremic high-risk patients are identified using the Identification of Seniors at Risk (ISAR) tool, which includes six straightforward dichotomous questions [ 7 ]. The research aims to determine the incidence of hyponatremia and the relative risk of ISAR score in elderly individuals.…”
Section: Introductionmentioning
confidence: 99%